2002
DOI: 10.1104/pp.004168
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalemma Abscisic Acid Perception Leads to RAB18Expression via Phospholipase D Activation in Arabidopsis Suspension Cells

Abstract: Abscisic acid (ABA) plays a key role in the control of stomatal aperture by regulating ion channel activities and water exchanges across the plasma membrane of guard cells. Changes in cytoplasmic calcium content and activation of anion and outward-rectifying K ϩ channels are among the earliest cellular responses to ABA in guard cells. In Arabidopsis suspension cells, we have demonstrated that outer plasmalemma perception of ABA triggered similar early events. Furthermore, a Ca 2ϩ influx and the activation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 52 publications
1
36
1
Order By: Relevance
“…This time course of PLD activation is similar to that observed for the response to abscisic acid (Hallouin et al, 2002) in Arabidopsis cells. The PLD activation was dependent on the dose of SA, with a maximum of response obtained with 250 mM SA.…”
Section: Discussion Pld Activation In Response To Sasupporting
confidence: 81%
“…This time course of PLD activation is similar to that observed for the response to abscisic acid (Hallouin et al, 2002) in Arabidopsis cells. The PLD activation was dependent on the dose of SA, with a maximum of response obtained with 250 mM SA.…”
Section: Discussion Pld Activation In Response To Sasupporting
confidence: 81%
“…In Arabidopsis suspension cells, we have demonstrated that ABA provoked RAB18 expression through stimulation of PLD activity (Jeannette et al, 1999;Hallouin et al, 2002). In this study, we show that DGPP is able to trigger the expression of three ABA up-regulated genes (At5g06760, LTI30, and RD29A) in addition to RAB18.…”
mentioning
confidence: 48%
“…This depolarization has been interpreted as the consequence of the activation of anion channels in stomatal guard cells of Vicia faba (Blatt, 1990;Schroeder and Keller, 1992;Thiel et al, 1992;Ward et al, 1995), Nicotiana benthamiana and Commelina communis (Schwartz et al, 1995;Leonhardt et al, 1999). In addition, we demonstrated that the extracellular perception of ABA in Arabidopsis suspension cells was necessary for the activation of anion channels inducing the plasma membrane depolarization (Ghelis et al, 2000a), and recently we showed that this anion channel stimulation induced by extracellular ABA perception was dependent on phospholipase D activities (Hallouin et al, 2002). In guard cells that are the most studied plant cell model used for the dissection of ABA signaling pathways (Assmann, 1993;Schroeder et al, 2001), two distinct anion channels, rapid anion channels (R-type) and slow anion channels (S-type), were proposed to participate in the plasma membrane depolarization (Schroeder and Keller, 1992;.…”
mentioning
confidence: 87%
“…This could suggest a role for the plasma membrane potential in the control of gene expression (Schaller and Frasson, 2001). In previous articles (Ghelis et al, 2000a;Hallouin et al, 2002), we showed that the induction of RAB18 gene expression in response to ABA was dependent on the ABA induced activation of anion channels. Since we now know that plasma membrane depolarization induced by ABA involved both anion channel activation and proton pumping reduction, we have now to determine what signal is responsible for the induction of the RAB18 gene expression: the variation of the anion currents or the plasma membrane depolarization induced by this anion current variation.…”
Section: Ca 21 Has a Dual Effect Leading To Plasma Membrane Depolarizmentioning
confidence: 99%